Pengelolaan Model Pembinaan Tahfidz Quran di SMA Muhammadiyah 18 Sunggal - Dahliana, Dahliana; Kasduri, Mario (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The purpose of analyzing this research data is to analyze the management of the tahfizd qur'an coaching model at SMA Muhammadiyah 18 Sunggal, what are the supporting factors in managing the tahfizd qur'an coaching model at SMA Muhammadiyah 18 Sunggal and what are the inhibiting factors in managing the tahfizd qur'an coaching model at SMA Muhammadiyah 18 Sunggal. Methods Data collection is done through observation, interviews, and documentation. To analyze the data, the writer uses a qualitative descriptive analysis technique, and data testing technique using triangulation method. The results of the study revealed that the application of the Qur'an tahfizd coaching model using the talqin model in memorizing the Qur'an at Muhammadiyah 18 Sunggal High School was started by reading the verses of the Qur'an, then continued by repeating verse by verse. The supporting factor in tahfizd Qur'an activities at SMA Muhammadiyah 18 Sunggal this activity was directly supported by the principal, and the enthusiasm of students in participating in the Qur'an tahfizd program and holding graduation at the end of the semester, which motivates students to be more active in memorizing the Qur'an.The inhibiting factor in this school is that there are still students who are not fluent in reading the Qur'an, this is due to the lack of cooperation between homeroom teachers and teachers of tahfizd Qur'an.